CASE STUDIES FROM DIFFERENT TYPES OF HEAT EXCHANGERS TO PLATE AND SHELL HEAT EXCHANGER: A REVIEW - Bandeira, V. F.; Pachekoski, W. M.; Mikowski, A. (Revista de Engenharia Térmica, 2020)
A Plate and Shell Heat Exchanger (PSHE) is manufactured with round welded plates in its core. These plates are designed to withstand high pressures and temperatures. Failures in this kind of heat exchanger were registered in a short operating period. To obtain the failure modes present in this equipment and a theoretical framework concerning this field of study, a research methodology was proposed (Systematic Literature Review – SLR) and a theoretical survey was carried out focusing in the 316L stainless steel and titanium grade 1 for its use in the Brazilian offshore industry. Seeing that the whole PSHE structure is welded, it is necessary to account for the strain caused by severe expansion processes in heat exchanger joints. This regarding, the laser welding process was investigated because of its narrow melting zone. It is believed that it was possible to clarify which failure modes are related to corrosive processes or stress concentration highlighting the structural and mechanical characterization models employed. Considering that the research field is relatively new, it was feasible to establish a theoretical basis of solutions applicable to PSHE, such as the use of more recessive material, reduce the corrosiveness of the operating medium, and reduce external sources of tension. Also, new content was assembled to assess the future decision-making process, regarding the design or maintenance of welded plate exchangers.